Content and Method of Information for Participants in Clinical Studies With Induced Pluripotent Stem Cells (iPSCs) - Orzechowski, Marcin; Schochow, Maximilian; Kühl, Michael; Steger, Florian (Frontiers in Cell and Developmental Biology, 2021)
Research with induced pluripotent stem cells (iPSCs) involves specific ethical challenges, which should be addressed in the informed consent process. Up to now, little concern has been paid to the practice of information in iPSC-clinical studies. In order to fill this research gap, we have searched the documentation of the Research Ethics Committee at Ulm University from the years 2007–2019. In our previous research, we have identified twelve items for evaluation of the process of information in iPSC research. We used these items to analyze content and form of information provided for participants in the iPSC studies conducted at Ulm University and Ulm University Hospital in Germany. All analyzed studies provide general information regarding the study’s aim, method, and collection of donor’s personal data and specimen. The information for participants in these studies adheres to general guidelines for research involving human subjects; however, in several areas fails to take into account the specific nature of research with iPSCs. The majority of analyzed studies fail to provide information about possible individual consequences connected with genetic research, such as the possibility of re-identification of the donor or incidental findings acquired during research. Missing is also information about the possibility of future studies involving reproductive research or transplantation of cells and organs. The donor information process in all analyzed studies is conducted in form of the information sheet and oral information. The results of our research show that the process of informed consent in iPSC research should be updated as new developments emerge in this area. However, comprehension of information should not be jeopardized through information overload. Effective communication of essential information requires improved information methods tailored to the needs of participants, such as video animations, interactive consent modules or social media instruments.